Decomposing Firm-level Sales Variation - Jakob R. Munch; Daniel X. Nguyen (University of Copenhagen, Economic Policy Research Unit (EPRU), 2009)
We measure the contribution of firm-specific effects to overall sales variation within a destination and find it remarkably low. Our empirical decomposition is structurally motivated by a heterogeneity model of exporting involving destination-specific, firm-specific, and firm-destination-specific latent effects with incidental truncation. We use a highly detailed dataset with exports by products and destinations for all Danish manufacturing firms. We find the contribution of firm-specific heterogeneity to within-destination sales variation varies greatly across HS6 products, and that for the median product it drives 31% of the sales variation. When we remove first-time exports from our sample, the median value increases to 40%, implying that firm-destination-specific effects are most important the first year. We conclude that while firm-specific productivity can account for some of the variation, the majority is explained by firm-destination-specific heterogeneity sources such as firm-destination-specific demand.
Keywords: F12; C24; 330; firm heterogeneity; firm-level export data; truncation correction; Exportwirtschaft; Verarbeitendes Gewerbe; Dekompositionsverfahren; Dänemark